MANAJEMEN KELAS UNTUK MENCEGAH PERUNDUNGAN VERBAL DI SD TUMBUH 3 YOGYAKARTA - Prastowo, Andi (Pascasarjana IAIN Kudus, 2017)
The issue of violent learning in Indonesia, one of them in the Special Province of Yogyakarta, has become a disturbing phenomenon in the last decade. Bullying is believed by some experts to be one of the root of the problem. There are three types of bullying, verbal, relational, and physical, but the most common is verbal abuse. Meanwhile, effective classroom management is one way that is believed to prevent and address the problem. One of the primary schools in Yogyakata city that has been quite successful in implementing this is the Tumbuh 3 Yogyakarta’s Elementary School (ES). This article discusses how the implementation of classroom management to prevent verbal abuse in Tumbuh 3 Yogyakarta’s ES. Through a case study with naturalistic approaches that collected data through in-depth interviews, moderate participant observation, and documentation found that implementation of classroom management to prevent verbal bullying in Tumbuh 3 Yogyakarta’s ES was conducted with an immediate response and a long-term response, anti-harassment with the application of Positive Behavioral Interventions and Supports.